Physical Organohydrogels With Extreme Strength and Temperature Tolerance - Zhang, Jing Wen; Dong, Dian Dian; Guan, Xiao Yu; Zhang, En Mian; Chen, Yong Mei; Yang, Kuan; Zhang, Yun Xia; Khan, Malik Muhammad Bilal; Arfat, Yasir; Aziz, Yasir (Frontiers in Chemistry, 2020)
Tough gel with extreme temperature tolerance is a class of soft materials having potential applications in the specific fields that require excellent integrated properties under subzero temperature. Herein, physically crosslinked Europium (Eu)-alginate/polyvinyl alcohol (PVA) organohydrogels that do not freeze at far below 0°C, while retention of high stress and stretchability is demonstrated. These organohydrogels are synthesized through displacement of water swollen in polymer networks of hydrogel to cryoprotectants (e.g., ethylene glycol, glycerol, and d-sorbitol). The organohydrogels swollen water-cryoprotectant binary systems can be recovered to their original shapes when be bent, folded and even twisted after being cooled down to a temperature as low as −20 and −45°C, due to lower vapor pressure and ice-inhibition of cryoprotectants. The physical organohydrogels exhibit the maximum stress (5.62 ± 0.41 MPa) and strain (7.63 ± 0.02), which is about 10 and 2 times of their original hydrogel, due to the synergistic effect of multiple hydrogen bonds, coordination bonds and dense polymer networks. Based on these features, such physically crosslinked organohydrogels with extreme toughness and wide temperature tolerance is a promising soft material expanding the applications of gels in more specific and harsh conditions.